2014
DOI: 10.1002/anie.201410322
|View full text |Cite
|
Sign up to set email alerts
|

Nickel‐Catalyzed Dehydrogenative Cross‐Coupling: Direct Transformation of Aldehydes into Esters and Amides

Abstract: By exploring a new mode of Ni-catalyzed cross-coupling, we have developed a protocol to transform both aromatic and aliphatic aldehydes into either esters or amides directly. The success of this oxidative coupling depends on the appropriate choice of catalyst and organic oxidant, including the use of either α,α,α-trifluoroacetophenone or excess aldehyde. We present mechanistic data that supports a catalytic cycle involving oxidative addition into the aldehyde C–H bond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
64
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(73 citation statements)
references
References 86 publications
5
64
0
Order By: Relevance
“…N ‐Butylcyclohexanecarboxamide (2) (CAS 128037–34–3): Prepared by using method A. Spectral data were in agreement with literature values. White solid (39 mg, 71 %), R f = 0.12 (10 % EtOAc in n ‐pentane).…”
Section: Methodssupporting
confidence: 77%
“…N ‐Butylcyclohexanecarboxamide (2) (CAS 128037–34–3): Prepared by using method A. Spectral data were in agreement with literature values. White solid (39 mg, 71 %), R f = 0.12 (10 % EtOAc in n ‐pentane).…”
Section: Methodssupporting
confidence: 77%
“…3n (B) The same transformation was performed on a gram scale (using a larger capsule), which delivered the ester product 27 in 97% yield. 3n (C) The Ni(cod) 2 capsules could be used to enable a host of other Ni-catalyzed reactions, such as Dong’s oxidative esterification and amidation methodologies, 46 our laboratory’s aryl C–N bond forming reactions, 3c and Fu’s sp 2 –sp 3 cross-coupling of alkyl halides. 47 (D) Paraffin capsules containing only Ni(cod) 2 or Ni(cod) 2 /SIPr combinations are being commercialized, which we expect will enable their more widespread use.…”
Section: From the Glovebox To The Benchtopmentioning
confidence: 99%
“…9,11,14a,2025 In each case, the original precatalyst was replaced with equimolar quantities of complex 1 ; the same stoichiometry of ligand was then used. Empirically, we found that the addition of K 3 PO 4 improved the reaction yields with precatalyst 1 , so it was included in reactions even if the original report did not do so.…”
mentioning
confidence: 99%